2022
DOI: 10.1096/fj.202101567r
|View full text |Cite
|
Sign up to set email alerts
|

Alpinetin inhibits macrophage infiltration and atherosclerosis by improving the thiol redox state: Requirement of GSk3β/Fyn‐dependent Nrf2 activation

Abstract: Alpinetin is a plant flavonoid isolated from Alpinia katsumadai Hayata with antioxidant and anti-inflammatory properties. Monocyte infiltration into the intima promotes atherosclerotic development and causes plaque instability at the later stage, which is profoundly influenced by various oxidants. In this study, we investigated whether alpinetin restores the redox state to inhibit monocyte infiltration and ameliorates atherosclerosis. ApoE-deficient (ApoE −/− ) mice were fed a high-fat diet and treated with al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…MMP2 has been implicated in the remodelling of the ECM to assist trophoblast cell invasion, and a previous study showed that enhancing MMP-2/9 activity could promote trophoblast cell invasion and migration [26]. Remarkably, Fyn was reported to facilitate cell invasion and migration by regulating MMP2 and MMP9 [27,28], which was in line with our results. MMP-2/9 activity was inhibited by knockdown of Fyn, which in turn was promoted by overexpression of Fyn.…”
Section: Discussionsupporting
confidence: 92%
“…MMP2 has been implicated in the remodelling of the ECM to assist trophoblast cell invasion, and a previous study showed that enhancing MMP-2/9 activity could promote trophoblast cell invasion and migration [26]. Remarkably, Fyn was reported to facilitate cell invasion and migration by regulating MMP2 and MMP9 [27,28], which was in line with our results. MMP-2/9 activity was inhibited by knockdown of Fyn, which in turn was promoted by overexpression of Fyn.…”
Section: Discussionsupporting
confidence: 92%
“…This finding was in line with a study that reported that AKT inactivation was closely involved in the process of DOX-induced cardiotoxicity [ 33 ]. AKT inactivation resulted in GSK3 β /FYN activation, thus promoting the nuclear exclusion of Nrf2 and its degradation in cytoplasm [ 34 ]. Here, we also reported that DOX decreased Nrf2 expression, and Mul treatment restored Nrf2 protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, diarylheptanoids yakuchinone A ( 4) and 5 0 -hydroxyyakuchinone A (5) scavenged reactive oxygen species (ROS) in HepG cells. 50 Moreover, 13-hydroxynootkatone (155) and nootkatone-11,12-epoxide (162) from A. oxyphylla effectively repaired the damage from tert-butyl hydroperoxide-induced oxidative stress in adipose-derived mesenchymal stem cells in a dose-dependent manner. 4 Coriandralpinins A-H (67-74) isolated from A. coriandriodora also exerted ROS inhibition in a dose-dependent manner.…”
Section: Anti-oxidant Effectsmentioning
confidence: 99%